Estrategia de comunicación y plan de medios para la Congregación Betesda Central - Vera Puedmag, Carla Yessenia (2014)
Central Betesda is a Christian Evangelical organization belonging to the delegation God's Assembly as institution of origin pentecostal. Betesda looks trasmitir for his vision and mission, by means of the use of the communication resources that they possess inside the managing of the department of communications. The present work of degree realizes a participative diagnosis by means of the use of tools and key technologies for the development of strategies of communication and plan of means, seeking to generate this way a suitable management of the communication inside the department of Betesda Central's communications and that this one benefits to the objective public of the organization.